Suicidal ideation during COVID-19 lockdown in Greece: Prevalence in the community, risk and protective factors. (March 2021) - Papadopoulou, Athanasia; Efstathiou, Vasiliki; Yotsidi, Vasiliki; Pomini, Valeria; Michopoulos, Ioannis; Markopoulou, Evaggelia; Papadopoulou, Marianna; Tsigkaropoulou, Evdoxia; Kalemi, Georgia; Tournikioti, Kalliopi; Douzenis, Athanasios; Gournellis, Rossetos
Highlights: The two-week prevalence of suicidal ideation in the Greek population was determined at the level of 5.2%. Mental health history, poor perceived quality of physical health, impaired family functioning, anxiety and depressive symptoms emerged among the risk factors of suicidal ideation. Positive feelings regarding the lockdown measures, resilience, relationship with friends and faith in a Supreme Being were determined as protective factors against suicidal ideation. The study offers a considerable reference point for future studies on suicidal ideation. Abstract: The aim of this study was to investigate the prevalence of suicidal ideation in the community as well as the risk and protective factors of suicidal ideation during restriction measures in Greece, after the outbreak of the COVID-19 pandemic. Α web-based anonymous survey was conducted during the first lockdown period. Participants completed the Generalized Anxiety Disorder scale (GAD-2), the Patient Health Questionnaire (PHQ-2), the Systemic Clinical Outcome and Routine Evaluation (SCORE-15), the Connor-Davidson Resilience Scale (CD-RISK-2), and a self-report questionnaire for COVID-19 pandemic-related data. From a total of 5, 116 adults included in the study, 5.20% reported suicidal thoughts, 14.17% were potential clinical cases of anxiety, and 26.51% of depression. Participants presented significantly higher suicidal ideation rates during the last two weeks of the lockdown compared to its previous two weeks. Unmarried or divorced marital status, mental health history, poor perceived quality of physical health, impaired family functioning, anxiety and depression symptoms were independently associated with higher odds of suicidal ideation, whereas higher resilience, positive feelings with regard to the lockdown measures, relationship with friends, and faith in a Supreme Being were associated with lower suicidal ideation odds. According to the findings, suicidal ideation prevalence might be considered elevated and its increase during the lockdown period alarming. The risk and protective factors identified in the study offer valuable information for the development of preventive strategies against suicidal ideation, especially in times of crisis.